Demonstration for wartime nurseries, 1942 (1942)
1942 1939-1945 "Demonstration for wartime nurseries, 1942" [T0167.jpg], 1942 This photograph is from 'Woman Power', a pamphlet issued by the London Women's Parliament, a conference of 983 representatives from the Women's Cooperative Guild, Housewives' Clubs, trade unions and voluntary and professional organisations. The conference discussed part time work, wages, child care training, and women in the services (including 'pram parades' for wartime nurseries, such as the one shown here).